Distribution and use of knowledge under the laws of the web - Josef Falkinger (Center for Economic Studies and ifo Institute (CESifo), 2007)
Empirical evidence shows that the perception of information is strongly concentrated in those environments in which a mass of producers and users of knowledge interact through a distribution medium. This paper considers the consequences of this fact for economic equilibrium analysis. In particular, it examines how the ranking schemes applied by the distribution technology affect the use of knowledge, and it then describes the characteristics of an optimal ranking scheme. The analysis is carried out using a model in which agents' productivity is based on the stock of knowledge used. The value of a piece of information is assessed in terms of its contribution to productivity.
Keywords: 330; Wahrnehmung; Informationsverbreitung; Ranking-Verfahren; Internet; Informationsverhalten; Informationsgesellschaft; Informationsökonomik; Theorie